Electrocardiogram of pure left ventricular hypertrophy and its differentiation from lateral ischaemia. Issue 3 (September 1981) - Beach, C; Kenmure, A C; Short, D
Abstract : In routine reporting of electrocardiograms, a frequent problem is presented by the presence of repolarisation abnormalities (ST depression and/or T wave inversion) in the lateral leads without the accepted QRS voltage criterion of left ventricular hypertrophy. To help resolve this problem, the electrocardiograms of 41 patients with severe aortic stenosis who had no evidence of coronary disease were compared with the electrocardiograms of 20 patients with lateral myocardial infarction who had no clinical evidence of left ventricular hypertrophy. Nine of the patients with aortic stenosis were found to show repolarisation abnormalities in the lateral leads without the standard voltage criterion of left ventricular hypertrophy. The repolarisation pattern of aortic stenosis could frequently be distinguished from that of coronary disease by the presence of one or more of the following five features: depression of the J point, asymmetry of the T wave with rapid return to the baseline, terminal positivity of the T wave ("over-shoot"), T inversion in V6 greater than 3 mm, and T inversion greater in V6 than in V4.